Learning Communities in the field of Education: Professional Development programme for Educators in KendriyaVidalaya Learning Community and Learning Outcomes - Gupta, Neelu (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The perception of schools as learning communities has attracted cumulative attentiveness and observation within the continuing professional education for teachers of Kendriya Vidalaya, in recent years. It is a concept which places particular emphasis upon the 'inner strength' of a school community and lures from the experiences and proficiency of staff, teachers, and pupils, within the school as a module of self-empowering mechanisms for transformation and development. Professional teamwork is important and can greatly improve teaching, instruction, and professional relationships in a school, but it falls short of producing a true community of learners. In contrast, a school learning community includes educators, students, parents, and community partner‟s work together to improve the school and enhance students' learning opportunities. This paper reports on the progress of the applicability of the notion of 'learning community' as an avenue for professional education of teachers in Kendriya Vidalaya. This paper will also focus on the aims of learning Community. A professional learning community that emphasizes the teamwork of principals, teachers, and staff to identify school goals, improve curriculum and instruction, reduce teachers' isolation, assess student progress, and increase the effectiveness of school programs. Such programs improve schools, strengthen families, and energize community support, and increase student achievement and success. This paper seeks to examine the notion of schools as Learning Communities, and to reclaim the educational components of the debate as a basis for the continuing professional education of educators and the simultaneous benefits for their students. In our view, professional development is learning. Professional development for the learning community is creating a learning community and the process is one of learning.